Determinants of Consumer Purchase Intentions on Halal Products - Ariestio Amrullah (Universitas Airlangga, 2023)
Indonesia is one of the countries with the highest Muslim population in the world. This affects the demand for halal products in various industrial sectors, including the food and beverage industry. The high demand for halal products in Indonesian food and beverage industry is a challenge for MUI, the party authorized to issue halal certification, according to an opportunity for business actors as the first link in distribution of goods to consumers. Cafetelo D-9 SMEs are very concerned about opportunities and challenges posed by demand for halal-verified products. This study aims to evaluate consumer perceptions of attitudes towards D-9 Salatiga products and consumer purchase intentions towards D-9 Salatiga products. Data was collected through simple random sampling and shared on social media. This research used Partial Least Squares within Structural Equation Model. Data processing was conducted using SmartPLS 3.0 software and the (SEM-PLS) method. The results of this study indicate that consumer knowledge about halal has a significant and favorable influence on purchase intention. Knowledge about halal has a big impact on attitudes, and attitudes have a big impact on consumer intention to buy. This research is expected to help SMEs as business actors to pay more attention to halal product certification given the enthusiasm and public response to halal food and beverage products.